2012
DOI: 10.1103/physrevlett.108.227203
|View full text |Cite|
|
Sign up to set email alerts
|

Symmetry of Orbital Order inFe3O4Studied by FeL2,3Resonant X-Ray Diffraction

Abstract: We studied the symmetry of the Fe 3d wave function in magnetite below the Verwey temperature T(V) with resonant soft-x-ray diffraction. Although the lattice structure of the low-temperature phase of Fe(3)O(4) is well described by the pseudo-orthorhombic Pmca with a slight monoclinic P2/c distortion, we find that the 3d wave function does not reflect the Pmca symmetry, and its distortion toward monoclinic symmetry is by far larger than that of the lattice. The result supports a scenario in which the Verwey tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The monoclinic lattice order of magnetite was non-resonantly probed at the (001) and (110) reflections with 800 eV and 1200 eV x-rays, respectively. Electronic order below T V is characterized by the appearance of a (00 1 / 2 ) ordering period and was selectively probed on resonance at the Fe L 3 -edge (hν = 707 and 708 eV) [24,25]. The CCD detector was used to record the data for the (00 1 / 2 ) reflection at the Fe L 3 -edge presented in Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monoclinic lattice order of magnetite was non-resonantly probed at the (001) and (110) reflections with 800 eV and 1200 eV x-rays, respectively. Electronic order below T V is characterized by the appearance of a (00 1 / 2 ) ordering period and was selectively probed on resonance at the Fe L 3 -edge (hν = 707 and 708 eV) [24,25]. The CCD detector was used to record the data for the (00 1 / 2 ) reflection at the Fe L 3 -edge presented in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…The figure also demonstrates that the behavior of the (110) lattice Bragg peak is identical to that of the (001). As the next step, we add the analysis of time-traces from the (00 1 / 2 ) electronic order diffraction intensity [23][24][25] Up to this point, we have shown that optical excitation launches a strongly coupled charge-lattice motion, locally destroying the trimeron order. Now we address the question whether this process can instigate metallic behavior.…”
mentioning
confidence: 99%
“…For this method it is important to take into account that there is a layer at the surface of single crystals which contributes to the absorption but not to the diffraction of the soft x-rays27. By studying the azimuthal dependence of the diffracted intensity it has been shown that the distortion of the 3d orbitals towards monoclinic symmetry is by far larger than that of the lattice28. Ultrafast melting of the charge-orbital order leading to the formation of a transient phase, which had not been observed in equilibrium, was observed with time-resolved RSXD with a free-electron laser29.…”
mentioning
confidence: 99%
“…[42][43][44] Through a series of works on the (00 1 2 ) c and (001) c reflections at the Fe L 2,3 resonance of Fe 3 O 4 , we have found that these reflections, indeed, contain direct information on the orbital and charge order below T V . [45][46][47] There is also a study of the (00 1 2 ) c reflection at the O K resonance with O 1s → 2p excitation and this reflection has been interpreted as a signature of a particular charge and orbital order at the oxygen site. 48 In a previous work 47 we investigated the azimuth angle and polarization dependence of the (00 1 2 ) c and (001) c reflections at the Fe L 2,3 resonance using a thin layer of magnetite partially detwinned by epitaxial growth on a stepped MgO(001) substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47] There is also a study of the (00 1 2 ) c reflection at the O K resonance with O 1s → 2p excitation and this reflection has been interpreted as a signature of a particular charge and orbital order at the oxygen site. 48 In a previous work 47 we investigated the azimuth angle and polarization dependence of the (00 1 2 ) c and (001) c reflections at the Fe L 2,3 resonance using a thin layer of magnetite partially detwinned by epitaxial growth on a stepped MgO(001) substrate. From azimuth and polarization analysis of the (00 1 2 ) c reflection intensities, the order in the 3d electronic state below T V was found to have a large monoclinic deformation.…”
Section: Introductionmentioning
confidence: 99%